Peran Masyarakat dalam Menarik Minat Kunjungan Wisatawan: Studi di Kampung Adat Prailiu Kabupaten Sumba Timur - Putri Nur Aini Afifa; M. Setyo Nugroho (Jurnal Pariwisata Nusantara (JUWITA), 2022)
This study aims to find out how the role and strategy of traditional village community prailiu attract tourist visit interest in east sumba regency. This study uses descriptive qualitative approach with three data collection techniques. First, field observation in traditional village Prailiu. Second, Interview with informants (pusposive sampling). Third, documentation that is related to traditional village prailiu. Data analysis technique uses SWOT analysis to formulate traditional village community strategy prailiu in attracting tourist visit interest in east sumba regency. This study shows that traditional village community has firm desire and commitment in developing tourism village. Then, there are a number of alternative strategies that have been formulated to attract tourist visit interest based on SWOT analysis namely : (1) S-O strategy such as tourism product development, Having a partnership with sector private, Increasing production quality of Tenun (woven fabric), increasing promotion and marketing. (2) S-T strategy such as making tourism package and conducting strengthen product packaging. (3) W-O strategy such as developing SDM, having partnership between woven fabric craftsman and expanding woven fabric marketing network. (4) W-T Strategy such as constructing public awareness, making serftification CHSE, providing health protocol training and providing training about tourism village management.